Rice plant waste reinforced polyurethane composites for use as the acoustic absorption material - KOÇAK, EMİNE DİLARA (ELSEVIER SCI LTD, 2021)
Over the last decade, with the development of technology, studies to reduce noise are increasing rapidly. It is known that flexible polyurethane foams, which are one of the most preferred materials in sound insulation, can be achieved even more superior properties with natural fiber reinforcement. With the use of natural waste in the studies carried out in this field, both ecological and economic benefits will be provided. In this study, it was decided to use rice plant waste as a reinforcement. Untreated fibers and the fibers treated with 10% NaOH for 15 min were subjected to FTIR analysis and examined morphologically with SEM. These fibers are incorporated into the flexible polyurethane foam in the proportion of 5%, 10%, 15% and 20% by weight and the composites were obtained. As a result of the mechanical tests, the tensile strength, elongation and elasticity module values of the composites were examined. Untreated and treated 5% fiber reinforced composites have been found to have the best performance. Their morphological structures were observed and their densities were calculated. Sound absorption performances were evaluated by considering the cell and pore structures and sizes and the densities of these composites. It has been determined treated 5% rice plant waste reinforced composite has the best sound absorption property. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Flexible polyurethane foam; Rice plant waste; Bio-fiber based composite; Alkali; Mechanical properties; Sound absorption